Foxa2‐venus fusion reporter mouse line allows live‐cell analysis of endoderm‐derived organ formation. Issue 8 (26th June 2013) - Burtscher, Ingo; Barkey, Wenke; Lickert, Heiko
<x xml:space="preserve">Abstract</x> The Foxa2‐winged helix/forkhead box transcription factor (TF) is absolutely required for endoderm formation and organogenesis. Foxa2 plays essential roles during lung, liver, pancreas, and gastrointestinal tract development and regulates cell‐type specific programs in the adult organism. To specifically address Foxa2 function during organ development and homeostasis, we generated a Foxa2‐Venus fusion (FVF) reporter protein by gene targeting in embryonic stem (ES) cells. The FVF knock‐in reporter is expressed under endogenous Foxa2 control and the fluorescent protein fusion does not interfere with TF function, as homozygous mice are viable and fertile. Moreover, the FVF protein localizes to the nucleus, associates with chromatin during mitosis, and reflects the endogenous Foxa2 protein distribution pattern in several tissues in heterozygous animals. Importantly, live‐cell imaging on single‐cell level of the FVF and Sox17‐Cherry fusion double knock‐in reporter ES cell line reveals the dynamics of endoderm TF accumulation during ES cell differentiation. The FVF reporter also allowed us to identify the endoderm progenitors during gastrulation and to visualize the different branching morphogenesis modes of the lung and pancreas epithelium in ex vivo embryo and organ cultures. In summary, the generation of the FVF reporter line adds an important new tool to visualize and analyse endoderm‐derived organ development and homeostasis on the cellular and molecular level. genesis 51:596–604. © 2013 Wiley Periodicals, Inc.